Clinical symptoms, diagnosis and outcome of septic encephalopathy - Zein, Ahmed Ragab; Algassab, Ayat Bagi; Almatrafi, Mada Salem; Kamal, Hawazen Atef; Alshenghiti, Abdulilah Mokhtar; Alqarni, Bandar Merzen; Ashoori, Ali Jaber; Albloushi, Faisal Abdulsalam; Alshaban, Mahmood Abdulla; Alshahrani, Asma Sulaiman; Dawoud, Mohammed Emran (International Journal Of Community Medicine And Public Health, 2022)
Septic encephalopathy (SE) is the most common complication of sepsis and a major cause of mortality and morbidity worldwide. It occurs in around two third of patients admitted with sepsis in the intensive care units. The objective of this review is to discuss clinical symptoms, diagnosis and outcomes in patients with SE. Robust research was conducted from online databases such as Google Scholar and Cochrane. Studies from the last ten years were included in our review. The pathophysiology of SE is highly dynamic where a complex sequence of events occurs as a host response to an extracranial infection. SE presents a myriad of symptoms ranging from an altered mental state with confusion, disorientation to a more severe presentation with delirium and impaired consciousness. Arriving to a diagnosis of SE requires a rigorous systemic and neurological investigation. Modalities such as neuromonitoring, neuroimaging, clinical biomarkers and mental assessment scales offer limited diagnostic value but can be utilized to co-relate clinical symptoms. It is associated with adverse outcomes such as a high rate of 28-day and 180-day mortality. The quality of life is poor in surviving patients. There is a dearth of original research on SE in the Arab region and worldwide. Major research, both as prospective and retrospective studies is essential to achieve improved management of SE. Therapeutic approaches should be tailored towards modulating pathophysiological processes of sepsis. Follow up studies based on 180 day follow ups should be used to study patient quality of life and outcomes.